RNA binding protein HuD contributes to β-cell dysfunction by impairing mitochondria dynamics - Hong, Youlim; Tak, Hyosun; Kim, Chongtae; Kang, Hoin; Ji, Eunbyul; Ahn, Sojin; Jung, Myeongwoo; Kim, Hong Lim; Lee, Jeong Hwa; Kim, Wook; Lee, Eun Kyung (Cell Death and Differentiation, 2020)
Imbalanced mitochondrial dynamics in pancreatic β-cells contributes to β-cell dysfunction in diabetes; however, the molecular mechanisms underlying mitochondrial dynamics in the pathology of diabetes are not fully elucidated. We previously reported the reduction of RNA binding protein HuD in pancreatic β-cells of diabetes. Herein, we demonstrate that HuD plays a novel role in the regulation of mitochondrial dynamics by promoting mitochondrial fusion. We show enhanced mitochondrial fragmentation in the pancreas of db/db mice and HuD KO mice. Downregulation of HuD increases the number of cells with fragmented mitochondria and reduces the mitochondrial activity determined by mitochondrial membrane potential and ATP production in mouse insulinoma βTC6 cells. HuD binds to 3′-untraslated region of mitofusin 2 (Mfn2) mRNA and positively regulates its expression. Ectopic expression of Mfn2 in βTC6 cells stably expressing short hairpin RNA against HuD (shHuD) restores HuD-mediated mitochondrial dysfunction. Taken together, our results suggest that HuD regulates mitochondrial dynamics by regulating Mfn2 level and its reduced expression leads to mitochondrial dysfunction in pancreatic β-cells.
Keywords: Animals; Cell Line; Diabetes Mellitus, Experimental; ELAV-Like Protein 4; Gene Expression Regulation; GTP Phosphohydrolases; Insulin-Secreting Cells; Mice, Knockout; Mitochondria; Mitochondrial Dynamics; Protein Binding; RNA, Messenger